1998
DOI: 10.1210/endo.139.4.5930
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sex Differences on the Renal Secretion of Organic Anions

Abstract: The kidney's responsiveness to male sexual hormones has been often neglected. Renal secretion of organic anions is higher in male than in female individuals; as a consequence, most of the xenobiotics that are excreted from the organism through this pathway are eliminated more rapidly by males than by female animals. To gain further insight into this issue, we studied in vitro and in vivo characteristics of the transport of p-aminohippurate (PAH), a suitable marker for this system, in male and female rats, unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 24 publications
3
31
0
Order By: Relevance
“…Furthermore, renal Oat1 mRNA expression in male rats tended to be higher than in females. This trend paralleled data reported by Reyes et al (1998) that identified more active PAH transport in male rat renal cortical slices when compared with female slices. Noting that the Oat1 mRNA expression was principally in kidney in this study (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, renal Oat1 mRNA expression in male rats tended to be higher than in females. This trend paralleled data reported by Reyes et al (1998) that identified more active PAH transport in male rat renal cortical slices when compared with female slices. Noting that the Oat1 mRNA expression was principally in kidney in this study (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, age and gender are known to influence pharmacokinetic parameters, such as clearance and half-life of many drugs, as well as the extent of and sensitivity to drug toxicity. Reyes et al (1998) demonstrated a gender difference in renal transport in which male rats transported more PAH than did females. Moreover, PAH half-life was extended in castrated male rats as compared with intact males.…”
mentioning
confidence: 97%
“…With respect to long-term regulation of renal organic anion transport, much less data are available. There is evidence that renal organic anion transport is regulated by sex steroids (27), which is now shown to be most probably due to regulation of Oat1 and Oat3 (4,22). Moreover, hyperuricemia was shown to reversibly downregulate Oat1 and Oat3 (14,15).…”
mentioning
confidence: 97%
“…With respect to long-term regulation of renal organic anion transport, fewer data are available. There is evidence that renal organic anion transport is regulated by sex steroids (10), which now is shown to be most probably due to regulation of OAT1 and OAT3 (11,12) and maybe OAT2 (12). Moreover, hyperuricemia was shown to reversibly downregulate OAT1 and OAT3 (13) in rats.…”
mentioning
confidence: 98%